PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERAN PERAWAT DALAM KOMUNIKASI ETIK PROFESI DAN IMPLIKASINYA TERHADAP BRANDING RUMAH SAKIT BUNDA - Septina, Selly; Trigono, Ahdun; Rinaldi, Enrico Adhitya (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
This study aims to analyze the influence of transformational leadership on nurses' roles in professional ethical communication and its implications for hospital branding at Bunda Margonda General Hospital, Depok. A mixed methods approach was applied, combining quantitative surveys using MLQ, NELQ, and Aaker & Keller's brand equity scales, and qualitative semi-structured interviews with head nurses, staff nurses, marketing managers, and returning patients. A total of 114 staff nurses were included using total sampling. Path analysis revealed that transformational leadership significantly affects nurses’ ethical communication (β = 0.278; p = 0.003), and ethical communication significantly impacts hospital branding (β = 0.424; p = 0.000). However, transformational leadership does not directly influence branding (p > 0.05), but rather through the mediating role of ethical communication. Qualitative triangulation supports this finding, highlighting that the leadership of head nurses in cultivating ethical culture greatly influences hospital image. The study recommends routine training in transformational leadership and ethical communication for nurses as a strategy to improve service quality and institutional image.